SYSTEMATIC LITERATURE REVIEW : SISTEM INFORMASI MONITORING ABSENSI SISWA BERBASIS WEB - Fajriansyah Fajriansyah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze the implementation and effectiveness of the Web-Based Student Attendance Monitoring Management Information System through the Systematic Literature Review (SLR) approach. The use of a web-based system in student attendance management offers various advantages, including ease of access, increased recording accuracy, and the ability to provide real-time notifications to parents. This study collects literature from 2019 to 2024 that is relevant to this topic through Google Scholar and is evaluated using predetermined inclusion and exclusion criteria. From the results of the analysis, it was found that the main features of the system include digital attendance recording, structured attendance data management, and attendance notifications for parents. This system has been shown to improve the efficiency of school administration and parental involvement, although there are challenges related to internet access and data security. In conclusion, the Web-Based Student Attendance Monitoring Management Information System makes a significant contribution to increasing the transparency and effectiveness of student attendance management, while facing several technical challenges that need to be considered in its implementation. Keywords: Information system; student attendance monitoring; web-based